2021
DOI: 10.3390/cancers13133126
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Antibody-Drug Conjugate-Based Therapy in Head and Neck Cancer: A Systematic Review

Abstract: Background: Antibody-drug conjugates (ADCs) are designed to deliver potent cytotoxic agents into tumor tissues. During the last two decades, a plethora of ADCs have been successfully developed and used for several indications, including hematologic and solid tumors. In this work, we systematically reviewed the progress in ADC development for the treatment of HNC. Methods: This review was registered in PROSPERO database. A comprehensive search was conducted following PRISMA guidelines and using PubMed, Scopus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…Similarly, ADCs targeting different surface markers (EGFR, c-MET, HER2, etc.) conjugated to the PBD toxin or the microtubule inhibitor Auristatin, did not progress due to toxicity concerns [ 14 ]. Only the EGFR inhibitor cetuximab and the PD-1/PD-L1 immune checkpoint inhibitors pembrolizumab, nivolumab, and durvalumab, improve survival in recurrent or metastatic HNSCC [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, ADCs targeting different surface markers (EGFR, c-MET, HER2, etc.) conjugated to the PBD toxin or the microtubule inhibitor Auristatin, did not progress due to toxicity concerns [ 14 ]. Only the EGFR inhibitor cetuximab and the PD-1/PD-L1 immune checkpoint inhibitors pembrolizumab, nivolumab, and durvalumab, improve survival in recurrent or metastatic HNSCC [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, immunotoxin translation to the clinic has been jeopardized by severe off-target toxicities, especially because of their high immunogenicity and reduced targeting capacity, which limits their long-term use in patients [ 12 , 13 ]. On the other hand, different ADCs have also been tested for the treatment of HNSCC, such as ABBV-321, an EGFR-targeting antibody conjugated to a pyrrolobenzodiazepine (PBD) dimer cytotoxic molecule [ 14 ]. Nevertheless, ADCs present important drug leakage during circulation, also limiting their clinical use [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Those components are connected using a linker with a specific binding ability (summarized in [ 28 ]). Currently, ADCs are investigated in head & neck cancer (e.g., Trastuzumab Deruxtecan—target: HER2; Losatuxizumab vedotin—target: EGFR) (summarized in [ 29 ]). Another ADC that is currently analyzed in head & neck squamous cell carcinoma is Sacituzumab Govitecan-hziy, which targets Trop-2 [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ADCs are investigated in head & neck cancer (e.g., Trastuzumab Deruxtecan—target: HER2; Losatuxizumab vedotin—target: EGFR) (summarized in [ 29 ]). Another ADC that is currently analyzed in head & neck squamous cell carcinoma is Sacituzumab Govitecan-hziy, which targets Trop-2 [ 26 , 29 ]. Future clinical studies have to investigate whether this Trop-2 ADC can add any benefit to the current standard of care.…”
Section: Discussionmentioning
confidence: 99%
“…However, their clinical applicability to treat head and neck cancers still is unclear. 60 Some limitations in this review should be mentioned such as the language barrier, due to all evidence found was published in English, which eliminated the inclusion of available evidence published in any other language. However, it is useful to highlight that no restrictions about languages were performed; moreover, since most evidence is published in English, it is more likely that evidence meeting the eligibility criteria is published in this language.…”
Section: Discussionmentioning
confidence: 99%